INTEGRASI PENJADUALAN PRODUKSI DAN PERAWATAN UNTUK MINIMISASI DOWNTIME MESIN (STUDI KASUS PADA SALAH SATU PERUSAHAAN GARMEN) - Felicia, Johana; Ginting, Meriastuti (Universitas Mercu Buana, 2014)
Abstract. One of the common problem manufacturing company used to have isproduction lateness. It is caused by the manufacturing company haven‘t had aneffective scheduling system. This study aim to integrate production andmaintenance scheduling that focused on critical machine. Critical machine ischosen based on lowest OEE value. Integer programming uses to determineoptimal value of downtime, production quantity, dan maintenance quantity. Theresult of this study shows that downtime can be decreased by 82.20 minutes. Itcauses increased OEE value up to 25.56%. Integrated production and maintenancescheduling also ensures that all production activity and maintenance activity canbe carried out in work time range and still, can fulfill demand.Keyword:Scheduling, Production, Maintenance, Overall EquipmentEffectiveness(OEE), Integer Programming